Implementasi dan Simulasi Jaringan Komputer untuk Meningkatkan Pemahaman Siswa SMA 1 Tajurhalang dalam Bidang Teknologi Informasi - Abdul Sidik; Akib Supandi; Farmin Wabula; Hasria Hasria; Reza Aqib Setyo Anggoro (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The advancement of network technology plays a crucial role in supporting modern education. This study aims to enhance students' understanding of network technology at SMA 1 Tajurhalang through a program of computer network implementation and simulation. The activities involve participatory training that includes the introduction of basic networking concepts, hands-on router configuration practices, and simulations of LAN, MAN, and WAN networks. Evaluation results indicate an improvement in students' ability to configure networks and solve related technical problems. These findings highlight the importance of technology training in preparing students for the digital era.